IMPLEMENTATION OF THE MISSOURI MATHEMATICS PROJECT (MMP) LEARNING MODEL ON STUDENT COGNITIVE LEARNING OUTCOMES - Salsabila, Sifa; Saeful Anwar, Agus; Fitriyani, Yani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2024)
This research was motivated by students' low mathematics learning outcomes as evidenced by the average learning outcome score being 4.1 out of a KKM score of 7.0. After observing, one of the problems faced is the lack of student involvement in the learning process. The solution to overcome this problem is the use of a learning model. This research aims to determine how implementing the Missouri Mathematics Project (MMP) learning model affects fourth-grade students' cognitive learning outcomes in fraction material. The method used in this research is a quantitative Pre-Experimental approach, a group post-test design. The subjects in this research were 27 fourth-grade students at Second Sidaraja State Elementary School. At the pretest stage, students' cognitive learning outcomes obtained an average score of 40.18; at the post-test stage, the average value obtained was 83.70. These results obtained a gain value of 0.74 with an increase of 43.52, which is included in the high category. Based on the results of the research and analysis that has been carried out, the Missouri Mathematics Project (MMP) learning model can improve students' cognitive learning outcomes. Implementing this learning model is hoped to help students hone their understanding and abilities to use various practice questions.